AUGMENTED REALITY BOOK PENGENALAN ORNMAEN TRADISIONAL BALI - I Made Tirta Murdika; Padma Nyoman Crisnapati; I Made Gede Sunarya; I Gede Mahendra Darmawiguna (Universitas Pendidikan Ganesha, 2014)
Balinese traditional ornaments as a local cultural heritage should be conserved and maintained. The purpose of this research was to utilize the technology by developing an application that could be used as a media to documentize and introducing the shapes and the types of Balinese traditional ornaments with more interactive and attractive way.The method used was development research. This research aimed to develop an Augmented Reality Book application about the Balinese traditional ornaments by using the waterfall model until the system testing phase. This application used vuforia libraries that could play sound and display the 3D objects of Balinese traditional ornaments in a real environment by using books and android based smartphones.The result of this research is a book contains the information and images related to the Blinese traditional ornaments and also functioned as a marker of android based Augmented Reality Book application that can display a part of Balinese architecture with Balinese ornaments on it in 3D objects above the marker, followed by spoken narrations which explain the ornament shown. This application can be used as a media to documentize, introduce and conserve the national culture.